2001
DOI: 10.1289/ehp.01109s3457
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting a community sample in collaboration with farmworkers.

Abstract: Few studies have examined health effects of pesticides in farmworkers, possibly because researchers perceive this population to be relatively inaccessible. We conducted an epidemiologic study of health effects among farmworkers in two towns in central Florida--Apopka and Pierson. Apopka is a suburb of Orlando with a diffuse farmworker community working in many crops, whereas Pierson is a small rural town with a tightly knit farmworker community working mainly in ferns. We collaborated with the Farmworker Assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…We conducted a cross-sectional study in central Florida in 1996Florida in -1997. Study participants were recruited in collaboration with the Farmworkers Association of Florida, a farmworker advocacy group (Kamel et al 2001). Our target population was members of the Community Trust Federal Credit Union and their spouses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a cross-sectional study in central Florida in 1996Florida in -1997. Study participants were recruited in collaboration with the Farmworkers Association of Florida, a farmworker advocacy group (Kamel et al 2001). Our target population was members of the Community Trust Federal Credit Union and their spouses.…”
Section: Methodsmentioning
confidence: 99%
“…It is affiliated with several community organizations, including the Farmworkers Association; many but not all of its members are farmworkers. Credit Union members were typical members of the local communities (Kamel et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Kamel et al (74) focus their discussion on the importance of community collaboration to identifying and recruiting a valid sample for an epidemiologic survey. Working with the Farmworker Association of Florida, and relying on the association members' expertise in knowing how to locate farmworkers in their region, the investigators were able to obtain a representative sample with an adequate response rate.…”
Section: Articles Presented In This Issuementioning
confidence: 99%
“…Learning from community members is not simply a means of showing respect for the community; it can show the researcher important variables or characteristics not previously considered. For example, the epidemiologic survey of Kamel et al (74) succeeded because community members knew how to locate individuals selected to be in the sample. The discussion by Quandt et al (72) of the PACE (Preventing Agricultural Chemical Exposure) project indicated they used several modes (in-depth interviews, community forums) to learn from the community.…”
Section: Articles Presented In This Issuementioning
confidence: 99%
See 1 more Smart Citation